2000
DOI: 10.1093/emboj/19.17.4555
|View full text |Cite
|
Sign up to set email alerts
|

Triphosphate structure of guanylate-binding protein 1 and implications for nucleotide binding and GTPase mechanism

Abstract: The interferon-gamma-induced guanylate-binding protein 1 (GBP1) belongs to a special class of large GTP- binding proteins of 60-100 kDa with unique characteristics. Here we present the structure of human GBP1 in complex with the non-hydrolysable GTP analogue GppNHp. Basic features of guanine nucleotide binding, such as the P-loop orientation and the Mg(2+) co-ordination, are analogous to those of Ras-related and heterotrimeric GTP-binding proteins. However, the glycosidic bond and thus the orientation of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 58 publications
5
145
0
1
Order By: Relevance
“…15,16 GBPs have a concentration-dependent intrinsic high-turnover GTPase activity. [17][18][19] In particular, based on the crystal structure of GBP-1 20,21 and on biochemical considerations, it was proposed that GBP-1 belongs to the group of large GTP-binding proteins such as Mx and dynamin, all of which have a similar domain composition and GTPase activity, although sequence homology is very low. 20 We have shown that GBP-1 is the key and selective mediator of the anti-proliferative effect of ICs on both microvascular and macrovascular endothelial cells in vitro and that GBP-1 expression was inversely related with cell proliferation in vessel endothelial cells of Kaposi's sarcoma (KS) in vivo.…”
Section: During Angiogenesis and Inflammatory Processes Endothelial mentioning
confidence: 99%
“…15,16 GBPs have a concentration-dependent intrinsic high-turnover GTPase activity. [17][18][19] In particular, based on the crystal structure of GBP-1 20,21 and on biochemical considerations, it was proposed that GBP-1 belongs to the group of large GTP-binding proteins such as Mx and dynamin, all of which have a similar domain composition and GTPase activity, although sequence homology is very low. 20 We have shown that GBP-1 is the key and selective mediator of the anti-proliferative effect of ICs on both microvascular and macrovascular endothelial cells in vitro and that GBP-1 expression was inversely related with cell proliferation in vessel endothelial cells of Kaposi's sarcoma (KS) in vivo.…”
Section: During Angiogenesis and Inflammatory Processes Endothelial mentioning
confidence: 99%
“…GBP1 is among a family of large GTPbinding proteins whose prototypes are the microtubule-associated dynamins that coordinate microtubule organization and mediate vesicle trafficking [39]. Members of the family include the interferon-induced GBPs [40], yeast VP and yeast mitochondrial MGM1 thought to be involved in partitioning of mitochondrial DNA [39]. The N-terminal residues (6-372) of CECR2 (Fig.…”
Section: Cecr2 (Aak15343)-mentioning
confidence: 99%
“…The N-terminal residues (6-372) of CECR2 (Fig. 9B) show a predicted structural homology with the extended α-helical Cterminal portion of human GBP1 that does not exhibit the correspondent GTP-binding domain, but corresponds to the Middle and GED (GTPase effector domain) domains of dynamin that are involved in assembly of the multi-subunit complexes involved in endocytosis, synaptic vesicle recycling, caveolae internalization and vesicular trafficking in general [40,41,42]. The Pfam search indicated a well-conserved AT-Hook motif within the GBP homology domain (CECR2 residues 198-210) (Fig.…”
Section: Cecr2 (Aak15343)-mentioning
confidence: 99%
“…Die Bindung von GTP an GBP-1 bewirkt eine Oligomerisierung, wodurch sich die intrinsische Hydrolyseaktivät des Proteins stark erhöht und GTP über GDP zu GMP und anorganischem Phosphat hydrolysiert wird (Prakash et al, 2000b;Schwemmle and Staeheli, 1994). GBP-1 hydrolysiert GTP unabhängig von Guaninnukleotid-Austauschfaktoren (GEF),…”
Section: Biochemische Eigenschaften Und Struktur Von Gbp-1unclassified